Metode Bermain Jawaban Untuk Meningkatkan Kemampuan Menulis Siswa Kelas II SDN 06 Kampung Baru Kecamatan Pariaman Timur Kota Pariaman - Yeni Suryanti (Jurnal Konseling dan Pendidikan, 2016)
Students are rarely highly motivated in Bahasa learning, including answer questions, give response to questions, and do discussion that can improve student’s writing skill. This research is aimed to determine whether the use of playing-answer method can improve student’s writing skill in Bahasa learning. This is a class action research in which 20 elementary students of grade III as subject. Data were obtained through observation, interview, and test of writing skill. There is improvement in each cycle. In cycle I, average score of student’s writing skill is 68 or 55%. Meanwhile in cycle II, average score of student’s writing skill is 77,5 or 80%. This result shows that playing-answer method can improve student’s writing skill in Bahasa learning.